Population Aging and Economic Growth in Malaysia: New Evidence using Panel Threshold Analysis - Abdul Karim, Zulkefly; Arif, Nur 'Alyaa; Karim, Bakri Abdul; Mohamad, Massita; Ishak, Ismahalil (ETIKONOMI, 2026)
Research Originality: This research contribution focuses on the panel threshold model to examine the non-linear relationship between population aging and economic development in Malaysia. Research Objectives: This study aims to investigate the impact of aging on state economic growth in Malaysia (comprising 13 states and two federal territories) from 2005 to 2021. Research Methods: This study employed a threshold regression to identify the minimum turning point of aging that significantly impacts the Malaysian state's economic growth, while controlling for other factors. Empirical Results: The results revealed a single threshold effect between aging and economic growth, indicating a nonlinear positive relationship. The labor force aged 15-64 years has a positive impact on states' economic development. Implications: Therefore, these findings underscore the importance of policymakers focusing on the turning point to achieve balanced economic growth. These new findings are crucial for policymakers as additional input for implementing government policies, especially the National Senior Citizens Policy (DWEN) and the Malaysian Population Policy, to stimulate sustainable economic growth in the Malaysian state. JEL Classification: C18, J13, J21, O4